Új megközelítési módok, kutatási irányok a nemzetközi egészségföldrajzban - Pál, Viktor (Közép-Európai Közlemények, 2009)
In the last decade a lot of changes were noticeable in geography of health. These changes were partly approach-like, and – on the other hand – the former topics increased. In the paper I survey the most important changes. I enhance the question of „place”, the role of social science theories, appearance of critical approach, and some new research subject and trend. I survey the theories’ influence on the new trends. In the course of this, I demonstrate the diseases’ political ecology, the nursing’s geography of health, the regional medicometry, the handicapped people’s geography of health. These patterns demonstrate the changes of the international geography of health. On the other hand, the paper hasn’t got the purpose of demonstrating the process of medical geography turning into geography of health.